The Implementation of Problem-Based Learning Model to Improve the Mathematical Literacy Skills of Grade X.1 Students at SMAN 7 Pekanbaru - Syarifah Nur Siregar; Nurhayeti Nurhayeti; Atma Murni (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
This study aimed to improve students’ mathematical literacy skills (MLS) through the implementation of the Problem-Based Learning (PBL) model in the topic of probability at Phase E. The subjects were Grade X.1 students of SMAN 7 Pekanbaru in the 2024/2025 academic year. This Classroom Action Research (CAR) was carried out in two cycles, namely Cycle I and Cycle II, each consisting of two meetings with the stages of planning, action, observation, and reflection. The research instruments comprised (1) learning materials, including the Learning Objectives Flow (ATP) and teaching modules, and (2) data collection instruments, including an MLS test and observation sheets for teacher and student activities. The findings revealed that the implementation of the PBL model successfully improved both the learning process and students’ MLS. The analysis of the MLS test results showed a significant improvement: the number of students in the “very good” category increased from 1 in the pre-test to 8 in Cycle I and 18 in Cycle II, while those in the “very poor” category decreased from 22 to 12 in Cycle I and only 2 in Cycle II. Therefore, the PBL model proved effective in improving the learning process and enhancing the mathematical literacy skills of SMAN 7 Pekanbaru students in the 2024/2025 academic year on the topic of probability.